Prescribing practices and attitudes toward giving children antibiotics. - Paluck, E. (2001)
OBJECTIVE: To investigate whether overprescribing is common in treatment of pediatric upper respiratory infections and to examine factors that influence prescribing antibiotics for children. DESIGN: A random, stratified sample of practising family physicians was surveyed with a mailed questionnaire. Initial nonresponders were mailed a second questionnaire. SETTING: British Columbia. PARTICIPANTS: A total of 608 general and family physicians. Response rate was 64%; 392/612 surveys were completed. MAIN OUTCOME MEASURES: Physicians' self-reported prescribing practices and knowledge of and attitudes toward using antibiotics for children's upper respiratory tract infections. RESULTS: Relative to treatment guidelines developed for the study, most physicians responded appropriately to the cough (94%) and lobar pneumonia (99.1%) vignettes. More than half the physicians (56.5%) reported they would immediately prescribe antibiotics for tympanic membrane dysfunction, and 79.4% indicated they would prescribe antibiotics for pharyngitis without obtaining a laboratory culture. Approximately 25% of physicians in the study did not believe that prior antibiotic use increased personal risk for acquiring drug-resistant infection, and 23.1% did not believe that antibiotic use was an important factor in promoting resistance in their communities. CONCLUSION: Education in current treatment of pediatric upper respiratory tract illnesses and antimicrobial drug resistance is required. The high response to the questionnaire (64%) and the many requests from physicians to receive the project's educational materials (45%) indicate a high level of interest in this subject.